Effect of a water, sanitation and hygiene program on handwashing with soap among household members of diarrhoea patients in healthcare facilities in Bangladesh: a cluster‐randomised controlled trial of the CHoBI7 mobile health program. Issue 8 (14th July 2020) - Zohura, Fatema; Bhuyian, Md. Sazzadul Islam; Saxton, Ronald E.; Parvin, Tahmina; Monira, Shirajum; Biswas, Shwapon K.; Masud, Jahed; Nuzhat, Sharika; Papri, Nowshin; Hasan, M. Tasdik; Thomas, Elizabeth D; Sack, David; et al.
Abstract: Objective: The Cholera‐Hospital‐Based‐Intervention‐for‐7‐days (CHoBI7) is a water treatment and handwashing with soap intervention for diarrhoea patients and their household members which is initially delivered in a healthcare facility setting. This study evaluated the effectiveness of CHoBI7 program delivery in increasing handwashing with soap in a healthcare facility setting among diarrhoea patients and their household members. Methods: A randomised controlled trial of the CHoBI7 program was conducted among 404 diarrhoea patients and their accompanying household members in healthcare facilities in Dhaka, Bangladesh. The 'Standard Message' Arm received the standard message given in Bangladesh to diarrhoea patients on the use of oral rehydration solution. The 'Health Facility Visit + Soapy Water' Arm received the standard message, the CHoBI7 communication module delivered bedside to the patient; and a soapy water bottle in the healthcare facility. The 'Health Facility Visit + Handwashing Station' Arm received this same intervention plus a small plastic handwashing station. Within 24 h of intervention delivery, three‐hour structured observation of handwashing practices at stool/vomit‐ and food‐related events (key events) was conducted in healthcare facilities of diarrhoea patients and their accompanying household members. Results: Compared to the Standard Message Arm, there was significantly more handwashing with soap at key events in both the Health Facility Visit + Soapy Water Arm (51% vs . 25 %) (Odds Ratio: 3.02; (95% Confidence Interval (CI): 1.41, 6.45) and the Health Facility Visit + Handwashing Station Arm (58% vs . 25%) OR: 4.12; (95% CI: 1.86, 9.14). Conclusion: These findings demonstrate that delivery of the CHoBI7 communication module and provision of a soapy water bottle to diarrhoea patients and their accompanying household members presents a promising approach to increase handwashing with soap among this high risk population in a healthcare facility setting in Bangladesh. Abstract : Objectif: Le programme (CHoBI7Cholera‐Hospital‐Based‐Intervention‐for‐7‐days) est une intervention de traitement de l'eau et de lavage des mains avec du savon pour les patients et les membres de leur famille qui est initialement administrée dans un établissement de santé. Cette étude a évalué l'efficacité du programme CHoBI7 pour augmenter le lavage des mains au savon dans les établissements de santé. Méthodes: Un essai contrôlé randomisé du programme CHoBI7 a été mené auprès de 404 patients atteints de diarrhée et des membres de leur famille qui les accompagnent dans des établissements de santé à Dhaka, au Bangladesh. Le bras "Message standard" a reçu le message standard donné au Bangladesh aux patients atteints de diarrhée sur l'utilisation de la solution de réhydratation orale. Le bras "Visite de l'établissement de santé + eau savonneuse" a reçu le message standard, le module de communication CHoBI7 a été délivré au chevet du patient et une bouteille d'eau savonneuse dans l'établissement de santé. Le bras "Visite de l'établissement de santé + station de lavage des mains" a reçu la même intervention, ainsi qu'une petite station de lavage des mains en plastique. Dans les 24 heures suivant l'intervention, une observation structurée de trois heures des pratiques de lavage des mains lors d'événements liés aux selles/vomis et à la nourriture (événements clés) a été menée dans les établissements de santé. Résultats: Par rapport au bras 'Message standard', le lavage des mains au savon était significativement plus fréquent lors des événements clés dans le bras 'Visite de l'établissement de santé + Station de lavage des mains' (58% contre 25%) (rapport de cotes (OR): 4, 12 ; (intervalle de confiance (IC) de 95%: 1, 86–9, 14) et dans le bras 'Visite de l'établissement de santé + Eau savonneuse' (51% contre 25%) (OR: 3, 02 ; (IC95% : 1, 41–6, 45). Conclusion: Ces résultats démontrent que l'implémentation du module CHoBI7 constitue une approche prometteuse pour augmenter le lavage des mains au savon dans un établissement de santé au Bangladesh.